Consumptive water footprints, water use efficiencies and productivities of rice under alternate wetting and drying for Kharagpur, West Bengal, India - A. Biswas (IWA Publishing, 2021)
An experimental study was carried out with medium duration rice variety (IR 36) during kharif and rabi seasons of 2015/16 and 2016/17 to investigate the effect of alternate wetting and drying (AWD) practice on water use efficiency, productivity, and consumptive water footprints of rice. The performance of AWD practice was compared with the conventionally (CON) irrigated rice using non-weighing lysimeters. The study resulted that by managing the alternate wetting and drying up to 15 cm below the ground level, a significant reduction in water input (26–29% in kharif and 22–27% in rabi season) could be achieved under AWD. A reduction in evapotranspiration (about 6% in both kharif and rabi seasons) was also observed under AWD. Reduction in consumptive water footprint (about 2–3% in kharif and 2–5% in rabi) was obtained under AWD. Reductions in blue water footprints (7% in kharif and 4–5% in rabi) was also observed under AWD. On average, crop water use efficiency was significantly enhanced by 27–33% and 20–29% in the respective kharif and rabi seasons under AWD practice. Significant improvement in total water productivity by 29–37% and 23–35% in the respective two seasons exhibited the superiority of AWD over CON during the two years of field experiments. HIGHLIGHTS Substantial reduction (22–29%) in water input was under AWD.; Rice evapotranspiration decreased by 6% under AWD.; AWD reduced rice consumptive water footprint by 2–5%.; A substantial increase (20–33%) in crop water use efficiency was under AWD.; AWD improved total water productivity considerably by 23–37%.;